UKRAINIAN HISTORIOGRAPHY: ACTIVITIES OF KEY FIGURES OF THE KYIV TERMINOLOGY CENTRE (LATE HALF OF THE XX – BEGINNING OF THE XXI CENTURY) - Voitovych, Оleh (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. We trace the urgent need for a complete historiographical description of the activities of Ukrainian terminological centres, as well as their significant figures, whose work laid the methodological foundations of Ukrainian terminology, since there is a great demand for overview and general information to understand the tradition and plan further development of Ukrainian terminology and terminography, clarify undeveloped problems and adequately popularise Ukrainian science outside Ukraine. Purpose. The purpose of the article is to fragmentarily describe the activities of key figures of the Kyiv scientific terminology centre in the second half of the XX and early XXI centuries. Results. The Kyiv Scientific Terminology Centre includes leading scholars from academic institutions and universities in Kyiv whose works have become fundamental in modern Ukrainian terminology, although this study does not claim to be complete. The article briefly outlines the main areas of activity of the key figures of this scientific centre, whose work has significantly influenced the development of modern Ukrainian terminology, taking into account the continuity of the national tradition and understanding of the future, innovative approaches. Among these scholars are V. Nimchuk, T. Kyiak, L. Symonenko, V. Ivashchenko, I. Kazimirova, and N. Artikutsa. The main principles of these scientists’ activities were the principles of nation-centrism, anthropocentrism, interdisciplinarity, linguistic expansionism, systematicity; their works actualised the synchronic-diachronic approach to the interpretation of linguistic facts, and presented the cognitive and functional-pragmatic newest paradigms of knowledge. Originality. The novelty of the study lies in the fact that, given the need to systematise terminological historiography, the activities of the Kyiv terminological centre are fragmentarily characterised, taking into account the most significant achievements of its key figures. Conclusion. It is shown that (1) V. Nimchuk developed in detail the foundations of onomastic terminology and terminography, and was a pioneer in developing a diachronic approach to the description of Ukrainian philological terms; (2) the activities of T. Kiyak’s work was focused on terminological and terminographic work not only in the projection on Ukrainian but also on other Slavic languages; the researcher focused on the development of technical terminology and provided valuable remarks on the ways of creating Ukrainian terms taking into account the theory of sociolinguistics on the basis of the tactics of term creation he systematised; (3) L. Symonenko left a considerable legacy in the field of terminology: she focused on the problems of the history of the development of Ukrainian linguistics, periodisation of this process, its analysis, interpretation of new approaches, and a specific contribution to the description of individual terminology systems in various fields of knowledge; (4) V. Ivashchenko made a lot of efforts to develop the theory of terminology and terminography. Ivashchenko, who for the first time in Ukrainian linguistics introduced cognitive terminology and systematically considered the problems and achievements of Ukrainian linguistics against the background of Slavic linguistics; (5) I. Kazymyrova actively continues the traditions in the development of terminology and terminography established by the Department of Terminology of the NASU, in particular, the researcher actively promotes Ukrainian terminological theory and practice outside Ukraine, and develops new approaches to the creation of a diachronic dictionary of Ukrainian linguistic terms; (6) Ukrainian legal terms are actively studied by N. Artykutsa, who has achieved success in their systematisation, standardisation and terminology. Her works can be a model for describing other terminological systems in various fields of knowledge.